Mycobacterium tuberculosis spoligotypes and drug susceptibility pattern of isolates from tuberculosis patients in peri-urban Kampala, Uganda - Asiimwe, Benon B.; Gunilla, Kallenius; Koivula, Tuija; Joloba, Moses L. (BMC infectious diseases, 2008)
The poor peri-urban areas of developing countries with inadequate living conditions and a high prevalence of HIV infection have been implicated in the increase of tuberculosis (TB). Presence of different lineages of Mycobacterium tuberculosis has been described in different parts of the world. This study determined the predominant strain lineages that cause TB in Rubaga division, Kampala, Uganda, and the prevalence of resistance to key anti-tuberculosis drugs in this community. This was a cross-sectional study of newly diagnosed sputum smear-positive patients aged ≥ 18 years. A total of 344 isolates were genotyped by standard spoligotyping and the strains were compared with those in the international spoligotype database (SpolDB4). HIV testing and anti-tuberculosis drug susceptibility assays for isoniazid and rifampicin were performed and association with the most predominant spoligotypes determined. A total of 33 clusters were obtained from 57 spoligotype patterns. According to the SpolDB4 database, 241 (70%) of the isolates were of the T2 family, while CAS1-Kili (3.5%), LAM9 (2.6%), CAS1-Delhi (2.6%) were the other significant spoligotypes. Furthermore, a major spoligotype pattern of 17 (4.5%) strains characterized by lack of spacers 15–17 and 19–43 was not identified in SpolDB4. A total of 92 (26.7%) of the patients were HIV sero-positive, 176 (51.2%) sero-negative, while 76 (22.1%) of the patients did not consent to HIV testing. Resistance to isoniazid was found in 8.1% of strains, while all 15 (4.4%) strains resistant to rifampicin were multi-drug resistant. Additionally, there was no association between any strain types in the sample with either drug resistance or HIV sero-status of the patients. The TB epidemic in Kampala is localized, mainly caused by the T2 family of strains. Strain types were neither associated with drug resistance nor HIV sero-status.